The Role of the Electricity Sector in the Economic Development of Egypt - S. N. Volkov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
Egypt is the most dynamically developing country in the region of North Africa. In the nearest future, it is expected to turn into the largest economy of Africa in terms of GDP measured by PPP and to overtake Nigeria. The leadership of Egypt considers accelerated development of the national energy complex, including electricity sector, as one of the main drivers of the economic growth. It will be based on the latest achievements of scientific and technological progress and new forms of attracting foreign direct investment, mainly concession agreements in the format of public-private partnership. This allows medium-sized companies to participate in the process of transnationalization that becomes one of its distinguishing features on the modern stage. The master plan for the development of the electric power industry until 2035 envisages the use of various traditional and renewable energy sources. It is planned to create a balanced electric power generation structure, overcoming the current bank tilt towards gasfired thermal power plants. It is expected that in the 2034/35 financial year coalfired power plants in Egypt will account for 34.0% of electricity generation, 19.4% for solar power plants (11.8% for photovoltaics and 7.6% for concentrated solar power), 19.4% for gas-fired power plants, 14.6% for wind power plants, 8.8% for nuclear power plants, 3.2% for hydro power plants and almost 0.6% for thermal power plants working on fuel oil. The objective of electricity sector’s development is the creation of an advanced branch of the economy, in which renewable energy sources and energy-efficient technologies play an important role, ensuring uninterrupted and reliable energy supply, as well as turning the country into a regional energy hub. All this will contribute not only to overcoming the crisis phenomena in the industry itself, observed since 2010s, but also to further change in the nature of the inclusion of the Egyptian economy in the system of the international division of labor, which has undergone significant changes over the past decades.